Accuracy of dynamic sentinel lymph node biopsy for inguinal lymph node staging in cN0 penile cancer - Juanito Gebruers; Laura Elst; Marcella Baldewijns; Liesbeth De Wever; Koen Van Laere; Maarten Albersen; Karolien Goffin (EJNMMI Research, 2023)
Abstract Background Penile cancer is characterized by an early lymphatic dissemination. In intermediate and high-risk primary tumors without palpable inguinal lymph nodes, there is a 6–30% risk of micro-metastatic disease. Invasive lymph node staging in these patients is performed using dynamic sentinel lymph node biopsy (DSNB). In this study, the role of DSNB in cN0 penile cancer was studied, evaluating features of sentinel lymph node (SN) visualization and outcome parameters. Patients with penile cancer without inguinal lymph node metastases who were referred for DSNB at our center between January 2015 and May 2021 and had a follow-up period of at least 18 months, were retrospectively included. After injection of 85 ± 20 MBq [99mTc]Tc-nanocolloid peritumorally, dynamic, static planar and SPECT/CT imaging was performed. Primary endpoints were sensitivity of the diagnostic procedure, disease-free survival and DSNB-related adverse events. Secondary endpoints were SN detection rate, number of SNs and the number of counts of the most active SN. Results Seventy-seven penile DSNB procedures in 75 patients (67 ± 11 years) were included. The detection rate of DSNB was 91% and 96% per procedure and groin, respectively. Sensitivity, specificity, negative predictive value (NPV) and positive predictive value (PPV) were 79%, 100%, 97% and 100%, respectively. More SNs were seen on SPECT/CT than on static planar imaging (1.33 vs. 1.17, p = 0.001). The mean counts per SN on static planar imaging was lower compared to SPECT/CT (1343 vs. 5008; p < 0.0001). There was a positive correlation between the total counts of the SN on the static planar image and the SPECT/CT (r = 0.79, p < 0.0001). Only one out of seventy-five patients (1%) experienced DSNB-related adverse events. After 18 months, 58 patients remained disease free (77%), 13 developed local recurrence (17%), and 4 developed lymphatic or distant metastases (5%). Conclusion DNSB is a safe diagnostic procedure with a good detection rate and in particular high negative predictive value. It can therefore prevent overtreatment of patients with negative inguinal groins on clinical examination and DSNB examination. Finally, DSNB enables an early detection of occult metastases which would not be visualized with standardized imaging modalities.